2019
DOI: 10.3390/s19224918
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation-Rate Control of Water Droplets on Flexible Transparent Heater for Sensor Application

Abstract: To develop high-performance de- or anti-frosting/icing devices based on transparent heaters, it is necessary to study the evaporation-rate control of droplets on heater surfaces. However, almost no research has been done on the evaporation-rate control of liquid droplets on transparent heaters. In this study, we investigate the evaporation characteristics of water droplets on transparent heater surfaces and determine that they depend upon the surface wettability, by modifying which, the complete evaporation ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…This is because the average evaporation flux of the droplet on the hydrophobic transparent heater surface is lower compared to that of the hydrophilic heater surface under the same conditions. 34,35 The average evaporation flux (J avg ) can be calculated using the equation below 36 i k j j j y…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because the average evaporation flux of the droplet on the hydrophobic transparent heater surface is lower compared to that of the hydrophilic heater surface under the same conditions. 34,35 The average evaporation flux (J avg ) can be calculated using the equation below 36 i k j j j y…”
Section: Resultsmentioning
confidence: 99%
“…As shown in the figure, it was confirmed that the droplet evaporation time on the hydrophobic transparent heater surface was noticeably delayed. This is because the average evaporation flux of the droplet on the hydrophobic transparent heater surface is lower compared to that of the hydrophilic heater surface under the same conditions. , The average evaporation flux ( J avg ) can be calculated using the equation below where ρ, A , V , and d V /d t are the density, surface area, volume, and rate of mass loss of the droplet, respectively. The droplet evaporation time of the droplet on the hydrophilic surface is less than that of the droplet on the hydrophobic surface due to the greater surface area of the droplet with the hydrophobic surface and is shown in Figure S8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 401 ] Furthermore, Park et al conducted an interesting study on the control of the evaporation rate of water droplets on THs, which had previously not been reported. [ 402 ] Kim et al combined a fluoropolymer nanocoating and Cu grids for robust and hydrophobic THs, which is helpful for icephobic and antifrost applications. [ 403 ] Another important aspect for the industrial integration of emerging THs is the assessment of the mechanical, chemical and optical properties of the substrates.…”
Section: Applicationsmentioning
confidence: 99%
“…Transparent heaters (THs) have been studied for multiple potential applications, including smart windows [1,2], defrosters [3,4], thermochromic displays [5,6], physical/ chemical sensors [7,8], and other advanced heat-generating systems [9][10][11]. High optical transparency and excellent electrical conductivity are two important factors for high-performance THs.…”
Section: Introductionmentioning
confidence: 99%